Development and performance test of a mechanical rice weeder attached to a narrow steel-wheeled tractor - Jantra, Chaiya; Sukcharoenvipharat, Watcharachan; Usaborisut, Prathuang; Thanpattranon, Pawin; Abdullakasim, Wanrat (International Journal of Agricultural and Biological Engineering, 2025)
A narrow steel-wheeled tractor was modified from a conventional rubber tire-wheeled tractor to facilitate the attachment of a chemical sprayer for paddy field use. A mechanical rice weeder was designed to attach to the tractor’s three-point hitch system, aiming to minimize environmental impacts. The developed mechanical weeder, 2 m wide×1.2 m long×1 m high, was attached to a narrow steel wheel tractor. It was designed to operate in 30-cm row spacing, working seven rows simultaneously. In the test results from 2, 40, and 60-day-old rice plants, the field capacities were 0.29, 0.29, and 0.35 hm2/h, resulting in 49.88%, 41.83%, and 44.62% field efficiencies, respectively. The weeding efficiencies were 61.36%, 63.68%, and 86.03%, while the average plant damage factors were 10.38%, 7.51%, and 4.85%, respectively. The fuel consumption was 7.02, 7.44, and 7.06 L/hm2, respectively. The slippage of the tractor was relatively high, at 27.33% and 27.12% for the 20- and 40-day-old rice plants, but was reduced to 10.56% after increasing the contact area of the narrow steel wheels for the 60-day-old rice plants. The performance index 1038.41 for the 60-day-old rice plants was the highest, attributed to a higher forward speed, compared to 305.84 for the 20-day-old and 460.33 for the 40-day-old rice plants. Key words: mechanical weeder; narrow steel wheel tractor; rice weedingDOI: 10.25165/j.ijabe.20251802.8309Citation: Jantra C, Sukcharoenvipharat W, Usaborisut P, Thanpattranon P, Abdullakasim W. Development and performancetest of a mechanical rice weeder attached to a narrow steel-wheeled tractor. Int J Agric & Biol Eng, 2025; 18(2): 165–168.